Cost‐Effectiveness Analysis of Using Loss of Heterozygosity to Manage Premalignant Oral Dysplasia in British Columbia, Canada. (11th July 2016) - Cromwell, Ian; Regier, Dean A.; Peacock, Stuart J.; Poh, Catherine F.
Abstract : Background: Management of low‐grade oral dysplasias (LGDs) is complicated, as only a small percentage of lesions will progress to invasive disease. The current standard of care requires patients to undergo regular monitoring of their lesions, with intervention occurring as a response to meaningful clinical changes. Recent improvements in molecular technologies and understanding of the biology of LGDs may allow clinicians to manage lesions based on their genome‐guided risk. Methods: We used a decision‐analytic Markov model to estimate the cost‐effectiveness of risk‐stratified care using a genomic assay. In the experimental arm, patients with LGDs were managed according to their risk profile using the assay, with low‐ and intermediate‐risk patients given longer screening intervals and high‐risk patients immediately treated with surgery. Patients in the comparator arm had standard care (biannual follow‐up appointments at an oral cancer clinic). Incremental costs and outcomes in life‐years gained (LYG) and quality‐adjusted life‐years (QALY) were calculated based on the results in each arm. Results: The mean cost of assay‐guided management was 8, 123 (95% confidence interval [CI] 2, 973 to 23, 062 in 2013 Canadian dollars) less than the cost of standard care. This difference was driven largely by reductions in resource use among people who did not develop cancer. Mean incremental effectiveness was 0.18 LYG (95% CI 0.08 to 0.39) or 0.64 QALY (95% CI 0.46 to 0.89). Sensitivity analysis suggests that these findings are robust to both expected and extreme variation in all parameter values. Conclusion: Use of the assay‐guided management strategy costs less and is more effective than standard management of LGDs. Implications for Practice: The findings of this study strongly suggest that the use of a risk‐stratification method such as a genomic assay can result in improved quality‐adjusted survival outcomes for patients with low‐grade oral dysplasia (LGD). The use of such an assay in this study provides "precision medicine, " allowing for a change in follow‐up frequency or early intervention as compared with current standard care. As genomic technologies become more common in cancer care, it is hoped that such an assay, once validated, will become part of a new model for the standard management of LGDs in similar health systems. Abstract : A decision‐analytic Markov model was used to estimate the cost‐effectiveness of risk‐stratified care using a genomic assay. Lower‐risk patients were given longer screening intervals, high‐risk patients were immediately treated with surgery, and controls had standard care (biannual follow‐up). The mean cost of assay‐guided management was 8, 123 less than the cost of standard care, largely because of reductions in resource use among people who did not develop cancer.